2022
DOI: 10.1038/s41586-022-05526-y
|View full text |Cite
|
Sign up to set email alerts
|

Primate gastrulation and early organogenesis at single-cell resolution

Abstract: Our understanding of human early development is severely hampered by limited access to embryonic tissues. Due to their close evolutionary relationship with humans, nonhuman primates are often used as surrogates to understand human development but currently suffer from a lack of in vivo datasets, especially from gastrulation to early organogenesis during which the major embryonic cell types are dynamically specified. To fill this gap, we collected six Carnegie stage 8–11 cynomolgus monkey (Macaca fascicularis) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 76 publications
(134 reference statements)
3
42
0
Order By: Relevance
“…4i). This analysis confirmed that during early stages (10, 12, and 14 hpf), NMP velocities point towards both mesoderm and neural tissue, whereas during later stages (16,19, and 24 hpf), they primarily point towards the mesoderm.…”
Section: Gene-expression Dynamics Suggest That Early Nmps Are Pluripo...supporting
confidence: 74%
See 2 more Smart Citations
“…4i). This analysis confirmed that during early stages (10, 12, and 14 hpf), NMP velocities point towards both mesoderm and neural tissue, whereas during later stages (16,19, and 24 hpf), they primarily point towards the mesoderm.…”
Section: Gene-expression Dynamics Suggest That Early Nmps Are Pluripo...supporting
confidence: 74%
“…To gain a better understanding of the temporal dynamics of NMPs during early development, we re-analyzed the RNA velocity data at individual time points (10,12,14,16,19, and 24 hpf). At 10 hpf (the end of gastrulation, beginning of axial extension -Fig.…”
Section: Gene-expression Dynamics Suggest That Early Nmps Are Pluripo...mentioning
confidence: 99%
See 1 more Smart Citation
“…Near identical cell populations can be found by analysis of existing mouse (E8.0-E8.5) 32 and macaque (CS9-CS11) 33 single-cell transcriptomic data highlighting the remarkable conservation of trunk formation across vertebrates ( Figure S3a-c ). However, the number of notochord cells in mouse were much lower than in chick and very few progenitors were captured, perhaps due to the small notochord size in mouse.…”
Section: Resultsmentioning
confidence: 90%
“…We followed the "Reduce, Reuse, Recycle" waste hierarchy, using the minimum sample size of 3 samples/group (n = 3/GF, n = 3/SPF, n = 3/CGF). This sample size is also commonly used in the single-cell analysis of murine brain tissues in previous studies [22,28,29,[34][35][36][37].…”
Section: Methods Ethics Statementmentioning
confidence: 99%